Lukisan Peleburan Cinta yang Erotik: Puisi Sufi di antara Estetika dan Etika Cinta Ilahiyah - Abdul Wachid B.S. (Al-Jami'ah Research Centre, 2005)
The ecstatic experience of a Sufi often drives him or her to producing such unusual sayings ordinarily called as shathiyya, which are sometimes problematic for common people. This is due to the fact that the expressions are not in common language; they are articulated in “the language of heart”, which is figurative and symbolic, since they state conative experiences. In this regard, love poems with their erotic expressions are chosen as a media for a Sufi’s reflection. In addition, the writer discusses the rationale of Sufis in connection with their erotic-love poetic illustrations. Some poems of Sufi Poets, such as those of Sana’i, Rabi‘a al-Adawiyya, Sa‘di, Jami‘,and Amir Hamzah, are elaborated for a further appreciation of the Sufis’ shathiyya.